2(v+1)=3v+23

Simple and best practice solution for 2(v+1)=3v+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(v+1)=3v+23 equation:


Simplifying
2(v + 1) = 3v + 23

Reorder the terms:
2(1 + v) = 3v + 23
(1 * 2 + v * 2) = 3v + 23
(2 + 2v) = 3v + 23

Reorder the terms:
2 + 2v = 23 + 3v

Solving
2 + 2v = 23 + 3v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-3v' to each side of the equation.
2 + 2v + -3v = 23 + 3v + -3v

Combine like terms: 2v + -3v = -1v
2 + -1v = 23 + 3v + -3v

Combine like terms: 3v + -3v = 0
2 + -1v = 23 + 0
2 + -1v = 23

Add '-2' to each side of the equation.
2 + -2 + -1v = 23 + -2

Combine like terms: 2 + -2 = 0
0 + -1v = 23 + -2
-1v = 23 + -2

Combine like terms: 23 + -2 = 21
-1v = 21

Divide each side by '-1'.
v = -21

Simplifying
v = -21

See similar equations:

| 3(x+5)+6=-6 | | 1/3x^2-10x | | -2a+7=-23 | | 3(y+4)-2y=2(y+1) | | (2x+4)9=(3x-30)9 | | 2(v+1)=3u+23 | | x=3x+6x-9 | | x^3-6x^2-20x+120=0 | | 4t+3m=1529 | | log^3=1 | | -2-5b+8b=-8(-3-6b)-5(8+6b) | | 6(-2)-y=-18 | | 6y=49-y | | 2a+a=39 | | 7w=w+18 | | -7v+6=-36 | | 6(3)-y=-18 | | 2.4=02 | | a+1-2a-1E+1=2 | | y=3x+6x-9 | | 8x-15y=0 | | a+b-(ab)=1 | | 6(2)-y=-18 | | ba=a+b+1 | | 3(c+3)+8=-10 | | 2[x+9]=x+22 | | a+b+2=ba | | -5a+4+6a=10-19 | | -3(2x+1)+20=8x+5 | | 384-6x^2=0 | | 5=20a | | 7x-3x+9=29 |

Equations solver categories